Permendikbudristek Number 30 of 2021: Reviewing Its Application and Relevance to Islamic Sharia Values in Aceh - Ade Kurniawan; M. Arif Idris; Azhari Azhari; Sulaiman Saputra (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This study analyzes the implementation of the national policy on the Prevention and Handling of Sexual Violence in Higher Education (Permendikbudristek 30/2021) and its relevance to Islamic Sharia values in Aceh, governed by the Qanun Jinayat. This duality presents a critical legal and practical challenge for state universities in the region. Using a qualitative method, this research investigated nine state universities in Aceh, collecting data from university leaders, Satgas teams, religious authorities, and students through interviews and documentation. The findings indicate that Permendikbudristek 30/2021 has been structurally implemented well, forming Satgas teams and improving student trust in reporting mechanisms. However, the core principle of consent in the regulation is a major point of contention, viewed by some groups as potentially conflicting with the Qanun Jinayat, which prohibits all extramarital sexual activity. To address this dilemma, several universities have adopted an adaptive approach by drafting derivative regulations involving scholars and community leaders to align the national policy with local Islamic law. This study emphasizes the complexity of integrating national protection policies with localized religious law. It recommends that policymakers and universities collaboratively develop contextual internal guidelines to strengthen victim protection while ensuring compliance with both national regulations and the Islamic Sharia prevailing in Aceh.